2021
DOI: 10.1111/adb.13014
|View full text |Cite
|
Sign up to set email alerts
|

Chronic opipramol treatment extinguishes cocaine craving through Rac1 in responders: A rat model study

Abstract: Ras‐related C3 botulinum toxin substrate 1 (Rac1), of the Rho small GTPase family, is a key regulator of actin cytoskeleton rearrangement and plays an important role in dendritic morphogenesis. Cocaine produces neuronal alterations, including structural changes in dendritic number and morphology. Emerging data indicate sigma‐1 receptors (σ‐1Rs) as a promising candidate for the prevention of cocaine craving. Opipramol is a σ‐1R agonist approved in some European countries for depression and anxiety. Here we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In our previous study using the same model, we demonstrated that there is no order effect in the reinstatement tests ( Bareli et al, 2021 ).…”
Section: The Rationale Of the Studymentioning
confidence: 72%
See 4 more Smart Citations
“…In our previous study using the same model, we demonstrated that there is no order effect in the reinstatement tests ( Bareli et al, 2021 ).…”
Section: The Rationale Of the Studymentioning
confidence: 72%
“…In addition, we found that those rats which responded to opipramol (Responders = Rs) exhibited significantly less Ras-related C3 botulinum toxin substrate 1 (Rac1) mRNA expression in the nucleus accumbens (NAc), compared with opipramol non-responder (NR) rats. Hence, we concluded that Rac1 differentiated Rs from NRs ( Bareli et al, 2021 ). A study by Tsai et al (2012) demonstrated that σ-1 receptor knock-down in the hippocampus is associated with a parallel downregulation of gamma-aminobutyric acid B receptor 1 (GABA B ,Gabbr1) and Rac1.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations